Hydrorefining catalyst and preparation method thereof
By optimizing the drying and calcining process of the hydrofining catalyst and using the multi-stage heating method, the problem of unbalanced catalyst performance in the prior art was solved, and the catalyst pore volume, specific surface area and strength were improved, and the overall performance of the catalyst was improved.
Patent Information
- Application Number
- CN202111239504.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-10-25
AI Technical Summary
The existing hydrofinishing catalyst production process conditions are poor, resulting in unbalanced pore volume, specific surface area and strength of the catalyst, affecting the quality of the final product.
By optimizing the conditions of the first drying, pre-calcination and second drying, the multi-stage heating method is used to dry and calcinate to ensure that the moisture volatility rate is at the optimal level and the pore volume, specific surface area and strength of the catalyst are controlled.
The pore volume, specific surface area and strength of the hydrorefining catalyst are improved, ensuring that the physical and chemical parameters of the catalyst are at a relatively good level, thereby improving the catalytic performance and service life of the catalyst.
Abstract
Description
Technical Field
[0001] The invention relates to the field of hydrorefining catalysts, and in particular to a hydrorefining catalyst and a preparation method thereof. Background Art
[0002] As environmental regulations become increasingly stringent, the quality standards of gasoline and diesel products are getting higher and higher. Among them, diesel hydrodesulfurization is an important means to improve diesel quality, so various types of hydrorefining catalysts are in great demand in the petrochemical field.
[0003] The conventional production process of hydrotreating catalysts is carrier molding → first drying and calcination of carriers → impregnation of active components → second drying and calcination of impregnated materials → finished catalysts. Currently, the performance parameters of the catalyst are optimized mainly by adjusting the raw materials, so as to produce hydrotreating catalysts with high pore volume, high strength and good particle size distribution.
[0004] For example, CN109794299A discloses a hydrogenation catalyst and a preparation method thereof. The catalyst comprises 0.8-4.6% molecular sieve and 15.4-41.2% heteropoly acid calculated as metal oxide. The catalyst can be used for distillate oil hydrofining and has high hydrogenation activity.
[0005] CN109718857A discloses a hydrorefining catalyst, its preparation method and application, and a method for hydrorefining distillate oil. The preparation method of the catalyst comprises mixing and calcining a precursor containing at least one of fluorine, silicon, zirconium, titanium, boron, magnesium, calcium and zinc and an alumina precursor to obtain an inorganic refractory component; mixing an alcohol, a carboxylic acid and an active component precursor to obtain an impregnation liquid, and mixing with the inorganic refractory component, forming and drying. The catalyst has a pore size of 100-300nm and has good performance.
[0006] CN109692693A discloses a hydrorefining catalyst and a preparation method thereof. The catalyst is firstly prepared by reacting a mixed solution A containing Ni, W and an auxiliary component with a sodium aluminate alkaline solution in parallel, aging the obtained slurry, then adding a mixed solution B containing W, Mo, Al and an auxiliary component and ammonia water in parallel to the aged slurry, then aging, and then drying, forming and other steps to prepare a hydrorefining catalyst.
[0007] Although the adjustment of catalyst raw materials and components can optimize the catalytic performance of the catalyst, the process conditions for catalyst preparation also play a key role in the various indicators of the finished catalyst and are related to the quality of the final product.
[0008] In order to further improve product quality, exploring the impact of various process conditions in the catalyst production process on product quality and optimizing the process steps have become the future trend of catalyst production. Summary of the invention
[0009] The purpose of the present invention is to overcome the problem of poor production process conditions of hydrotreating catalysts in the prior art and to provide a method for preparing a hydrotreating catalyst. The method can improve the pore volume, specific surface area and strength of the prepared hydrotreating catalyst by optimizing the conditions of the first drying, pre-calcination and second drying.
[0010] In order to achieve the above object, the present invention provides a method for preparing a hydrotreating catalyst, wherein the method comprises:
[0011] 1) subjecting the extruded carrier wet strip to first drying, pre-calcining and first calcining in sequence to obtain a catalyst carrier;
[0012] 2) impregnating the catalyst support prepared in step 1);
[0013] 3) performing a second drying and a second calcination on the catalyst support after the impregnation treatment in step 2) in sequence,
[0014] The first drying conditions include: drying at 40-70°C for 10-20 min, drying at 50-80°C for 15-25 min, drying at 60-90°C for 20-30 min, drying at 70-100°C for 20-30 min, and drying at 80-110°C for 30-40 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage;
[0015] The pre-calcination conditions include: calcination at 130-170°C for 15-25min, calcination at 190-230°C for 30-40min, calcination at 240-280°C for 40-60min, calcination at 290-310°C for 50-70min, and calcination at 310-330°C for 50-60min, and the latter stage calcination temperature is higher than the former stage calcination temperature;
[0016] The second drying conditions include: drying at 25-35°C for 20-30 min, drying at 30-40°C for 30-40 min, drying at 40-50°C for 35-45 min, drying at 45-55°C for 35-45 min, and drying at 50-60°C for 25-35 min, and the latter drying temperature is higher than the former drying temperature.
[0017] Preferably, the first drying conditions include: drying at 50-60°C for 10-20 min, drying at 60-70°C for 15-25 min, drying at 70-80°C for 20-30 min, drying at 80-90°C for 20-30 min, and drying at 90-100°C for 30-40 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage.
[0018] Preferably, the pre-calcination conditions include: calcining at 140-160°C for 15-25 min, calcining at 210-230°C for 30-40 min, calcining at 270-280°C for 40-60 min, calcining at 295-305°C for 50-70 min, and drying at 315-325°C for 50-60 min, and the latter stage calcination temperature is higher than the former stage calcination temperature.
[0019] Preferably, the second drying conditions include: drying at 25-30°C for 20-30 min, drying at 30-35°C for 30-40 min, drying at 40-45°C for 35-45 min, drying at 45-50°C for 35-45 min, and drying at 50-55°C for 25-35 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage.
[0020] Preferably, the extruded carrier wet strip contains a base material, an extrusion aid and a molding aid.
[0021] Preferably, the base material is selected from aluminum hydroxide dry rubber powder and / or silicon hydroxide dry rubber powder.
[0022] Preferably, the extrusion aid is selected from sesbania powder and / or methylcellulose.
[0023] Preferably, the molding aid is selected from one or more of citric acid, silica sol aqueous solution and nitric acid aqueous solution.
[0024] Preferably, the concentration of the silica sol aqueous solution is 20-35% by weight.
[0025] Preferably, the concentration of the nitric acid aqueous solution is 50-70% by weight.
[0026] Preferably, the amount of the extrusion aid is 1-5 parts by weight relative to 100 parts by weight of the base material.
[0027] Preferably, the amount of the molding aid is 15-20% by weight relative to 100 parts by weight of the base material.
[0028] Preferably, the shape of the extruded carrier wet strip is one or more of a spherical shape, a strip shape and a sheet shape.
[0029] Preferably, the extruded carrier wet strip is in a strip shape.
[0030] Preferably, the impregnation treatment is carried out in an impregnation liquid.
[0031] Preferably, the active component in the impregnation solution is selected from one or more of tungsten, molybdenum, nickel, cobalt and phosphorus.
[0032] Preferably, the content of the active component is 30-60 wt %, preferably 50-60 wt %, relative to the total weight of the impregnation solution.
[0033] Preferably, the immersion conditions include: immersion temperature of 20-35°C and time of 0.6-1h.
[0034] Preferably, the amount of the impregnation liquid is 1-2 parts by weight, preferably 1.5-1.8 parts by weight, relative to 1 part by weight of the catalyst carrier.
[0035] Preferably, the first calcination conditions include: a first calcination temperature of 500-1000° C., and a first calcination time of 1-5 h.
[0036] More preferably, the first calcination conditions include: the first calcination temperature is 600-800° C., and the first calcination time is 2-4 hours.
[0037] Preferably, the second calcination conditions include: the second calcination temperature is 300-800° C., and the second calcination time is 1-5 h.
[0038] More preferably, the second calcination conditions include: the second calcination temperature is 350-600° C., and the second calcination time is 1.5-4 h.
[0039] The second aspect of the present invention provides a hydrotreating catalyst prepared by the method described in the first aspect of the present invention.
[0040] Preferably, the pore volume of the hydrotreating catalyst is above 0.4 g / cm³, preferably 0.4-0.45 g / cm³.
[0041] Preferably, the specific surface area of the hydrotreating catalyst is above 160 m² / g, preferably 165-190 m² / g.
[0042] Preferably, the radial crushing strength of the hydrotreating catalyst is above 19 N / mm, preferably 21-25 N / mm.
[0043] Through the above technical solution, by controlling the first drying condition of the carrier and using a multi-stage temperature increase method for drying, the water volatilization rate can be ensured to be at an optimal level, thereby ensuring the strength of the catalyst carrier. At the same time, by controlling the volatilization rate of water, the pore volume and specific surface area of the catalyst can also be effectively controlled.
[0044] In addition, by pre-calcining the catalyst before calcining and pre-calcining the catalyst under multi-stage heating conditions, the pore volume and specific surface area of the catalyst can be ensured to be at a high level, and the catalyst strength can be further improved.
[0045] The second drying is carried out in a multi-stage method after impregnation, which can ensure the strength of the prepared catalyst while ensuring that it has a high pore volume and specific surface area. DETAILED DESCRIPTION
[0046] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0047] One aspect of the present invention provides a method for preparing a hydrotreating catalyst, the method comprising:
[0048] 1) subjecting the extruded carrier wet strip to first drying, pre-calcining and first calcining in sequence to obtain a catalyst carrier;
[0049] 2) impregnating the catalyst support prepared in step 1);
[0050] 3) performing a second drying and a second calcination on the catalyst support after the impregnation treatment in step 2) in sequence,
[0051] The first drying conditions include: drying at 40-70°C for 10-20 min, drying at 50-80°C for 15-25 min, drying at 60-90°C for 20-30 min, drying at 70-100°C for 20-30 min, and drying at 80-110°C for 30-40 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage;
[0052] The pre-calcination conditions include: calcination at 130-170°C for 15-25min, calcination at 190-230°C for 30-40min, calcination at 240-280°C for 40-60min, calcination at 290-310°C for 50-70min, and calcination at 310-330°C for 50-60min, and the latter stage calcination temperature is higher than the former stage calcination temperature;
[0053] The second drying conditions include: drying at 25-35°C for 20-30 min, drying at 30-40°C for 30-40 min, drying at 40-50°C for 35-45 min, drying at 45-55°C for 35-45 min, and drying at 50-60°C for 25-35 min, and the latter drying temperature is higher than the former drying temperature.
[0054] The inventors of the present invention have found in a large number of studies and practices that the drying and calcining conditions used in the preparation process of the existing hydrorefining catalyst and its carrier have a great influence on the performance of the prepared catalyst. For example, due to different drying conditions, the volatilization speed of water in the material is different, which will have a great impact on the strength of the carrier. If the water evaporates too slowly, the material is prone to adhesion and balling, which is not conducive to subsequent production; if the water evaporates too quickly, the material is prone to cracking, and the strength will be greatly reduced, thereby affecting the particle size distribution in the subsequent production process.
[0055] In the preparation of existing hydrotreating catalysts, the drying step is generally carried out by a one-stage constant temperature drying method, that is, drying is carried out at a constant temperature for a required time. As a result, it is difficult to control the physical and chemical parameters of the prepared hydrotreating catalyst to be within an ideal range, resulting in the prepared hydrotreating catalyst having performance defects to varying degrees.
[0056] Therefore, the inventors of the present invention have made adjustments to the drying process and other processes in the preparation process of the hydrotreating catalyst, that is, a multi-stage heating method is adopted in the first drying, pre-calcination and second drying processes of the present invention, thereby ensuring that the pore volume, specific surface area and strength and other properties of the prepared catalyst are at a relatively optimal level.
[0057] Hereinafter, the method for preparing the hydrotreating catalyst according to the first aspect of the present invention will be described in detail.
[0058] In the present invention, the equipment for performing multi-stage first drying and second drying can be a steam drying belt. The equipment is divided into multiple sections, the temperature of each section can be set differently, and the materials can be transported between the sections by a conveying device, so that the materials to be dried can be dried in multiple sections in different temperature ranges.
[0059] In the present invention, the equipment for pre-baking can be an electric heating drying belt, which is divided into multiple sections, each section can have different temperatures, and materials can be transported between sections by a conveying device, so that the materials to be baked can be baked in multiple sections in different temperature ranges.
[0060] According to a first aspect of the present invention, the extruded wet strip of the carrier is sequentially subjected to first drying, pre-calcination and first calcination to prepare a catalyst carrier.
[0061] In the present invention, the preparation method of the carrier wet strip is not particularly limited, and various conventional methods in the art can be used for preparation. For example, the extrusion raw materials of the carrier wet strip can be kneaded and then subjected to basic molding by an extrusion molding machine.
[0062] In the present invention, the carrier wet strip may contain a base material, an extrusion aid, a molding aid, etc., without particular limitation.
[0063] Wherein, the base material can be selected from aluminum hydroxide dry rubber powder and / or silicon hydroxide dry rubber powder, preferably aluminum hydroxide dry rubber powder.
[0064] The extrusion aid may be selected from sesbania powder and / or methyl cellulose; preferably sesbania powder.
[0065] The molding aid may be selected from one or more of citric acid, silica sol aqueous solution and nitric acid aqueous solution, preferably silica sol aqueous solution and nitric acid aqueous solution.
[0066] The concentration of the silica sol in the silica sol aqueous solution may be 20-35% by weight, and the concentration of the nitric acid aqueous solution may be 50-70% by weight, without any particular limitation.
[0067] In the present invention, the amount of the extrusion aid and the molding aid used is not particularly limited and can be selected conventionally in the art. For example, the amount of the extrusion aid can be 1-5 parts by weight relative to 100 parts by weight of the base material. The amount of the molding aid can be 15-20 parts by weight relative to 100 parts by weight of the base material.
[0068] According to the present invention, the shape of the extruded wet carrier strip is not particularly limited and can be selected according to specific needs. For example, the shape of the extruded wet carrier strip can be one or more of a sphere, a strip and a sheet. Preferably, the shape of the extruded wet carrier strip is a strip. More preferably, the strip is a three-leaf clover strip or a four-leaf clover strip.
[0069] In the present invention, the extruded wet strip of the carrier is first dried. The first drying can remove moisture from the wet strip of the carrier, thereby preventing the catalyst carrier from cracking during the subsequent preparation process.
[0070] According to the present invention, the first drying conditions include: drying at 40-70°C for 10-20 min, drying at 50-80°C for 15-25 min, drying at 60-90°C for 20-30 min, drying at 70-100°C for 20-30 min, and drying at 80-110°C for 30-40 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage.
[0071] Preferably, the first drying conditions include: drying at 50-60°C for 10-20 min, drying at 60-70°C for 15-25 min, drying at 70-80°C for 20-30 min, drying at 80-90°C for 20-30 min, and drying at 90-100°C for 30-40 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage.
[0072] By carrying out the first drying under the above conditions, it is possible to prevent the wet strips of the carrier from sticking and balling, which is beneficial to the subsequent smooth production, and to prevent the water from volatilizing too quickly, prevent the carrier from cracking, ensure the strength of the carrier, and at the same time increase the pore volume and specific surface area of the prepared hydrotreating catalyst, thereby improving the catalytic performance of the prepared catalyst.
[0073] In the present invention, in order to further prevent the carrier from cracking, improve the strength of the carrier and ensure the pore volume and specific surface area of the prepared hydrotreating catalyst, a pre-calcination treatment is performed after the first drying.
[0074] According to the present invention, the conditions of the pre-calcination treatment include: calcining at 130-170°C for 15-25min, calcining at 190-230°C for 30-40min, calcining at 240-280°C for 40-60min, calcining at 290-310°C for 50-70min, and calcining at 310-330°C for 50-60min, and the latter stage calcination temperature is higher than the former stage calcination temperature.
[0075] Preferably, the pre-calcination conditions include: calcining at 140-160°C for 15-25 min, calcining at 210-230°C for 30-40 min, calcining at 270-280°C for 40-60 min, calcining at 295-305°C for 50-70 min, and calcining at 315-325°C for 50-60 min, and the latter stage calcination temperature is higher than the former stage calcination temperature.
[0076] If the conventional one-stage treatment method is used for pre-calcination, it is difficult to ensure that the pore volume and strength of the prepared catalyst are at a good level due to the constant pre-calcination temperature. In the present invention, by performing the pre-calcination treatment in the above steps, on the one hand, the pore volume of the prepared hydrorefining catalyst can be ensured to be large, so that the catalyst has a good bulk ratio; on the other hand, the strength of the catalyst can be improved.
[0077] According to the present invention, the pre-calcined material is subjected to a first calcination to obtain a catalyst carrier.
[0078] Since the pore volume, specific surface area and strength of the carrier are basically guaranteed in the above-mentioned pre-calcination process in the present invention, the first calcination can be carried out under conventional conditions.
[0079] The first calcination conditions may include: a first calcination temperature of 500-1000° C., and a first calcination time of 1-5 h; preferably, the first calcination conditions include: a first calcination temperature of 600-800° C., and a first calcination time of 2-4 h.
[0080] According to the present invention, the catalyst carrier prepared as above is subjected to an impregnation treatment.
[0081] The immersion treatment may be carried out by conventional methods in the art without particular limitation.
[0082] The impregnation treatment can be carried out in an impregnation solution, and the impregnation solution can be prepared according to a conventional preparation method in the art without special restrictions. The impregnation solution contains active components, and preferably, the active components can contain one or more of tungsten, molybdenum, nickel, cobalt and phosphorus.
[0083] In the present invention, the content of the active component may be 30-60% by weight, preferably 50-60% by weight, relative to the total weight of the impregnation solution.
[0084] In the present invention, there is no particular limitation on the conditions for the impregnation, which may include: an impregnation temperature of 20-35°C and a time of 0.6-1h; preferably, the impregnation conditions include: an impregnation temperature of 25-30°C and a time of 0.6-0.8h. This can further improve the effect of the impregnation and ensure the catalytic performance of the prepared hydrorefining catalyst.
[0085] In the present invention, the amount of the impregnation liquid can be 1-2 parts by weight, more preferably 1.5-1.8 parts by weight, relative to 1 part by weight of the catalyst carrier, thereby making the impregnation more complete and further improving the catalytic performance of the hydrotreating catalyst obtained by impregnation.
[0086] According to the present invention, the catalyst support after the impregnation treatment is subjected to a second drying.
[0087] The second drying is carried out by a multi-stage heating method. Therefore, after the immersion treatment in the impregnation liquid, there is moisture in the gaps of the catalyst carrier. At this time, the treatment conditions of the second drying will still have a great impact on the strength and other properties of the catalyst.
[0088] Therefore, in the present invention, the conditions for the second drying include: drying at 25-35°C for 20-30 min, drying at 30-40°C for 30-40 min, drying at 40-50°C for 35-45 min, drying at 45-55°C for 35-45 min, and drying at 50-60°C for 25-35 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage.
[0089] Preferably, the second drying conditions include: drying at 25-30°C for 20-30 min, drying at 30-35°C for 30-40 min, drying at 40-45°C for 35-45 min, drying at 45-50°C for 35-45 min, and drying at 50-55°C for 25-35 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage.
[0090] By carrying out the second drying under the above conditions, it can be ensured that the catalyst after impregnation has good catalyst strength, pore volume and specific surface area.
[0091] According to the present invention, after the second drying, the second roasting can be carried out under normal conditions. The conditions of the second roasting are not particularly limited. For example, the conditions of the second roasting may include: the second roasting temperature is 300-800°C, and the second roasting time is 1-5h; preferably, the conditions of the second roasting include: the second roasting temperature is 350-600°C, and the second roasting time is 1.5-4h.
[0092] In the present invention, by performing the first drying, pre-calcination and second drying under the above conditions, the pore volume, specific surface area and strength of the prepared hydrotreating catalyst can be ensured to be at a good level, thereby further ensuring the catalytic performance and service life of the prepared hydrotreating catalyst.
[0093] The second aspect of the present invention provides a hydrotreating catalyst prepared by the method described in the first aspect of the present invention.
[0094] According to the second aspect of the present invention, the pore volume of the hydrotreating catalyst can reach 0.4 cm³ / g, preferably 0.4-0.45 cm³ / g.
[0095] The specific surface area of the hydrotreating catalyst can reach 160m² / g or more, preferably 165-190m² / g.
[0096] The radial crushing strength of the hydrotreating catalyst may be as high as 19 N / mm or more, preferably 21-25 N / mm.
[0097] The present invention will be described in detail below through examples.
[0098] In the following examples, the pore volume is measured by the method described in Q / SH 361 913;
[0099] The specific surface area is measured by the method described in GB / T5816.
[0100] The radial crushing strength is measured by a catalyst strength tester. The specific measurement method is as follows:
[0101] Take a section of catalyst sample and place it flat on the top of the strength meter piston. Press the "work key" and the piston will automatically and slowly descend to press on the sample until the sample breaks. Then the piston will automatically rise and display the pressure reading when the catalyst sample is crushed. This reading is the crushing strength of a single sample. Measure the crushing strength of 12 samples in the same way and remove the maximum and minimum values.
[0102] Calculate the radial crushing strength K in N / mm according to the following formula:
[0103] / 10
[0104] Where: P i It is the value of the pressure gauge reading when the sample is broken, in N / cm 2 ; S is the piston area of the strength tester, the value is 1, the unit is cm 2 ; L i It is the length of the sample in mm.
[0105] In the following examples and comparative examples, unless otherwise specified, the raw materials used are conventional commercially available products.
[0106] In the following embodiments and comparative examples, the drying device used in the first drying process was purchased from Huanggang Zhongzhou Anda Thermal Equipment Co., Ltd., model D-2021; the drying device used in the second drying process was purchased from Huanggang Huayao Zhongrui Kiln Co., Ltd., model F-2021; the roasting device used in the pre-roasting process was purchased from Huanggang Zhongzhou Anda Thermal Equipment Co., Ltd., model F-2102.
[0107] Preparation Example 1: Preparation of carrier wet strips
[0108] 350kg of aluminum hydroxide dry rubber powder, 16kg of sesbania powder, 25kg of nitric acid aqueous solution, 35kg of silica sol aqueous solution and 265kg of water were fully kneaded, wherein the concentration of the nitric acid was 65% by weight and the concentration of the silica sol aqueous solution was 32% by weight, and then the mixture was sent to an extruder for extrusion molding to obtain clover-shaped carrier wet strips with a length of 15-18mm.
[0109] Preparation Example 2: Preparation of impregnation solution
[0110] 200 kg of molybdenum trioxide, 26 kg of phosphoric acid and 70 kg of basic nickel carbonate were added to 500 kg of water, mixed and stirred, and then heated at 100° C. for 1 hour to prepare an impregnation solution.
[0111] Example 1
[0112] 1) The wet carrier strip prepared in Preparation Example 1 was subjected to a multi-stage first drying treatment, wherein the specific conditions are: drying at 55° C. for 15 min, drying at 65° C. for 20 min, drying at 75° C. for 25 min, drying at 85° C. for 25 min, and drying at 95° C. for 35 min in sequence;
[0113] 2) pre-calcining the carrier after the first drying treatment in step 1), the specific conditions are: calcining at 150°C for 20 minutes, calcining at 220°C for 35 minutes, calcining at 260°C for 50 minutes, calcining at 300°C for 60 minutes, and calcining at 320°C for 55 minutes;
[0114] 3) performing a first calcination on the carrier pre-calcined in step 2), wherein the calcination conditions are: calcination at 700° C. for 4 h;
[0115] 4) The catalyst carrier prepared after calcination in step 3) is placed in the impregnation solution prepared in Preparation Example 2 for impregnation, wherein the amount of the impregnation solution is 1.6 parts by weight relative to 1 part by weight of the catalyst carrier, the impregnation temperature is 30° C., and the impregnation time is 0.7 h;
[0116] 5) subjecting the product after the impregnation treatment in step 4) to a second drying, wherein the specific conditions are: drying at 25° C. for 20 min, drying at 30° C. for 30 min, drying at 40° C. for 35 min, drying at 45° C. for 35 min, and drying at 50° C. for 25 min;
[0117] 6) The product obtained in step 5) after the second drying treatment is subjected to a second calcination, and the calcination conditions are: temperature 370° C. and time 4 hours.
[0118] The hydrotreating catalyst S1 was prepared. After testing, the pore volume of S1 was 0.45 cm³ / g, the specific surface area was 172 m² / g, and the strength was 24.5 N / mm.
[0119] Example 2
[0120] 1) The wet carrier strip prepared in Preparation Example 1 was subjected to a multi-stage first drying treatment, wherein the specific conditions are: drying at 50° C. for 10 min, drying at 60° C. for 15 min, drying at 70° C. for 20 min, drying at 80° C. for 20 min, and drying at 90° C. for 30 min in sequence;
[0121] 2) pre-calcining the carrier after the first drying treatment in step 1), with the specific conditions being: calcining at 140°C for 15 min, calcining at 210°C for 30 min, calcining at 270°C for 40 min, calcining at 295°C for 50 min, and calcining at 315°C for 50 min;
[0122] 3) performing a first calcination on the carrier pre-calcined in step 2), wherein the calcination conditions are: calcination at 720° C. for 3 h;
[0123] 4) The catalyst carrier prepared after calcination in step 3) is placed in the impregnation solution prepared in Preparation Example 2 for impregnation, wherein the amount of the impregnation solution is 1.6 parts by weight relative to 1 part by weight of the catalyst carrier, the impregnation temperature is 30° C., and the impregnation time is 0.7 h;
[0124] 5) subjecting the product after the impregnation treatment in step 4) to a second drying, wherein the specific conditions are: drying at 28° C. for 25 min, drying at 32° C. for 35 min, drying at 42° C. for 40 min, drying at 48° C. for 37 min, and drying at 53° C. for 28 min;
[0125] 6) The product obtained in step 5) after the second drying treatment is subjected to a second calcination, and the calcination conditions are: temperature 390° C. and time 3.5 h.
[0126] The hydrotreating catalyst S2 was prepared. After testing, the pore volume of S2 was 0.42 cm³ / g, the specific surface area was 166 m² / g, and the strength was 22 N / mm.
[0127] Example 3
[0128] 1) The wet carrier strip prepared in Preparation Example 1 was subjected to a multi-stage first drying treatment, wherein the specific conditions are: drying at 60° C. for 20 min, drying at 70° C. for 25 min, drying at 80° C. for 30 min, drying at 90° C. for 30 min, and drying at 100° C. for 40 min in sequence;
[0129] 2) pre-calcining the carrier after the first drying treatment in step 1), the specific conditions are: calcining at 160°C for 25 min, calcining at 230°C for 40 min, calcining at 280°C for 60 min, calcining at 305°C for 70 min, and calcining at 325°C for 60 min;
[0130] 3) performing a first calcination on the carrier pre-calcined in step 2), wherein the calcination conditions are: calcination at 680° C. for 5 h;
[0131] 4) The catalyst carrier prepared after calcination in step 3) is placed in the impregnation solution prepared in Preparation Example 2 for impregnation, wherein the amount of the impregnation solution is 1.6 parts by weight relative to 1 part by weight of the catalyst carrier, the impregnation temperature is 30° C., and the impregnation time is 0.7 h;
[0132] 5) subjecting the product after the impregnation treatment in step 4) to a second drying, wherein the specific conditions are: drying at 30° C. for 30 min, drying at 35° C. for 40 min, drying at 45° C. for 45 min, drying at 50° C. for 45 min, and drying at 55° C. for 35 min in sequence;
[0133] 6) The product obtained in step 5) after the second drying treatment is subjected to a second calcination, and the calcination conditions are: temperature of 500° C. and time of 3 h.
[0134] The hydrotreating catalyst S3 was prepared. After testing, the pore volume of S3 was 0.41 cm³ / g, the specific surface area was 167 m² / g, and the strength was 21.3 N / mm.
[0135] Comparative Example 1
[0136] The method of Example 1 is followed, except that
[0137] In step 1), the conditions for the first drying treatment are constant temperature drying, the drying temperature is 100° C., and the drying time is 3 h.
[0138] The hydrotreating catalyst D1 was prepared. After testing, the pore volume of D1 was 0.39 cm³ / g, the specific surface area was 155 m² / g, and the strength was 18.5 N / mm.
[0139] Comparative Example 2
[0140] The method of Example 1 is followed, except that
[0141] In step 2), the pre-baking treatment conditions are constant temperature pre-baking, the pre-baking temperature is 250° C., and the pre-baking time is 3 hours.
[0142] The hydrotreating catalyst D2 was prepared. After testing, the pore volume of D2 was 0.37 cm³ / g, the specific surface area was 152 m² / g, and the strength was 17.5 N / mm.
[0143] Comparative Example 3
[0144] The method of Example 1 is followed, except that
[0145] In step 5), the second drying treatment is carried out under constant temperature drying, the drying temperature is 120° C., and the drying time is 3 h.
[0146] The hydrotreating catalyst D3 was prepared. After testing, the pore volume of D3 was 0.38 cm³ / g, the specific surface area was 155 m² / g, and the strength was 16.5 N / mm.
[0147] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a hydrotreating catalyst, characterized in that: The method includes: 1) subjecting the extruded carrier wet strip to first drying, pre-calcining and first calcining in sequence to obtain a catalyst carrier; 2) impregnating the catalyst support prepared in step 1); 3) performing a second drying and a second calcination on the catalyst support after the impregnation treatment in step 2) in sequence, The first drying conditions include: drying at 40-70°C for 10-20 min, drying at 50-80°C for 15-25 min, drying at 60-90°C for 20-30 min, drying at 70-100°C for 20-30 min, and drying at 80-110°C for 30-40 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage; The pre-calcination conditions include: calcination at 130-170°C for 15-25min, calcination at 190-230°C for 30-40min, calcination at 240-280°C for 40-60min, calcination at 290-310°C for 50-70min, and calcination at 310-330°C for 50-60min, and the latter stage calcination temperature is higher than the former stage calcination temperature; The second drying conditions include: drying at 25-35°C for 20-30 min, drying at 30-40°C for 30-40 min, drying at 40-50°C for 35-45 min, drying at 45-55°C for 35-45 min, and drying at 50-60°C for 25-35 min, and the latter drying temperature is higher than the former drying temperature.
2. The method according to claim 1, wherein: The first drying conditions include: drying at 50-60°C for 10-20 min, drying at 60-70°C for 15-25 min, drying at 70-80°C for 20-30 min, drying at 80-90°C for 20-30 min, and drying at 90-100°C for 30-40 min, and the drying temperature in the latter stage is higher than the drying temperature in the former stage.
3. The method according to claim 1, wherein: The pre-calcination conditions include: calcination at 140-160°C for 15-25min, calcination at 210-230°C for 30-40min, calcination at 270-280°C for 40-60min, calcination at 295-305°C for 50-70min, and drying at 315-325°C for 50-60min, and the latter stage calcination temperature is higher than the former stage calcination temperature.
4. The method according to claim 1, wherein: The second drying conditions include: drying at 25-30°C for 20-30 min, drying at 30-35°C for 30-40 min, drying at 40-45°C for 35-45 min, drying at 45-50°C for 35-45 min, and drying at 50-55°C for 25-35 min, and the latter drying temperature is higher than the former drying temperature.
5. The method according to any one of claims 1 to 4, wherein: The extruded carrier wet strip contains a base material, an extrusion aid and a molding aid.
6. The method according to claim 5, wherein: The base material is selected from aluminum hydroxide dry rubber powder and / or silicon hydroxide dry rubber powder; The extrusion aid is selected from sesbania powder and / or methylcellulose; The molding aid is selected from one or more of citric acid, silica sol aqueous solution and nitric acid aqueous solution.
7. The method according to claim 6, wherein: The concentration of the silica sol aqueous solution is 20-35% by weight; The concentration of the nitric acid aqueous solution is 50-70% by weight.
8. The method according to claim 5, wherein: The amount of the extrusion aid is 1-5 parts by weight relative to 100 parts by weight of the base material; Relative to 100 parts by weight of the base material, the amount of the molding aid is 15-20% by weight.
9. The method according to any one of claims 1 to 4, wherein: The shape of the extruded carrier wet strip is one or more of a sphere, a strip and a sheet.
10. The method according to any one of claims 1 to 4, wherein: The impregnation treatment is carried out in an impregnation liquid; The active component in the impregnation solution is selected from one or more of tungsten, molybdenum, nickel and cobalt.
11. The method according to claim 10, wherein: The content of the active component is 30-60% by weight relative to the total weight of the impregnation solution; The conditions of the immersion treatment include: an immersion temperature of 20-35° C. and an immersion time of 0.6-1 h; The amount of the impregnation liquid is 1-2 parts by weight relative to 1 part by weight of the catalyst carrier.
12. The method according to any one of claims 1 to 4, wherein: The first calcination conditions include: the first calcination temperature is 500-1000° C., and the first calcination time is 1-5 h; The second calcination conditions include: the second calcination temperature is 300-800° C., and the second calcination time is 1-5 hours.
13. A hydrotreating catalyst prepared by the method according to any one of claims 1 to 12.
14. The hydrotreating catalyst according to claim 13, wherein The pore volume of the hydrotreating catalyst is greater than 0.4 g / cm³; The specific surface area of the hydrotreating catalyst is greater than 160 m² / g; The radial crushing strength of the hydrotreating catalyst is greater than 19 N / mm.
15. The hydrotreating catalyst according to claim 14, wherein The pore volume of the hydrotreating catalyst is 0.4-0.45 g / cm³; The specific surface area of the hydrotreating catalyst is 165-190 m² / g; The radial crushing strength of the hydrotreating catalyst is 21-25 N / mm.
Citation Information
Patent Citations
Hydrorefining catalyst and preparation method thereof
CN109692693A
Hydrotreating catalyst, preparation method and applications thereof, and hydrotreating method of distillate oil
CN109718857A
Hydrogenation catalyst and preparation method thereof and distillate oil hydrogenation refining method
CN109794299A
Aromatic hydrogenation catalyst, preparation method thereof and aromatic hydrogenation catalytic method
CN103041831A
Hydrotreating catalyst for residual oil and preparation method for hydrotreating catalyst for residual oil
CN106914250A